0,999... = 1? Everything I wrote is false... Between stories and paradoxes - de Oliveira, Marta Elaine; Clareto, Sônia Maria [UNESP] (FapUNIFESP (SciELO), 2024)
0.999... = 1? A question triggers stories, in this article, in a math classroom. With each tithe, a story is brought. The stories are part of the production of a research that is being carried out during the postdoctoral internship in Education, which intends to investigate the mathematics class, focusing on teacher training through the production of thoughts through writing. As field data production, mathematics-related learning stories are welcome in different school contexts. For this text, stories of learning with mathematics rehearse, amid equality of 0.999... and 1. Events that invade and invent different dimensions of life productions and ways of relating to school mathematics. In the processes of and with writing, paradoxes are understood, along with Deleuze, as the passion of thought. There is a risk of walking in both directions at the same time: true and false, real and invented, beginning and end. Dismembering the subject: the good thinker.
0,999... = 1? Tudo que escrevi é falso... Entre histórias e paradoxos
Keywords: Learnings; Mathematics; Passion; Thought; Writing